Oral Anticoagulant Therapy and its Control: Marcumar (Phenprocoumon), a new highly active Anticoagulant and Konakion (Phytomenadione), as an Effective Regulator - Brambel, Charles E; Lawrence Serra, G (Thrombosis and Haemostasis, 1959)
Data are presented to demonstrate the advantages of Marcumar in short-term and long-term treatment, over less active anticoagulants, and the effectiveness of Konakion as regulator of such therapy.